The Regulation of Lymph Node Pre-Metastatic Niche Formation in Head and Neck Squamous Cell Carcinoma - Hu, Chen; Huang, Qiang; Sun, Qing (Frontiers in Oncology, 2022)
In many distinct forms of malignancies, there is a close relationship between lymph node (LN) metastases and further dissemination to distant organs, and this is a critical prognostic factor. At the beginning of the process, the original tumor secretes soluble substances or releases extracellular vesicles (EVs) that are carried through lymphatic channels to draining (sentinel) LN. The tumor-derived factors then drive LN remodeling. These significant alterations occur prior to the emergence of the first metastatic cell, bringing about the development of a pre-metastatic niche that allows metastatic cells to survive and thrive. In this review, we discuss current information available about the regulation of lymph node pre-metastatic niche in head and neck squamous cell carcinoma (HNSCC), and the role of EVs in forming the pre-metastatic niche.